SYNTHETIC CHILD SEXUAL ABUSE MATERIAL AND INDIAN CRIMINAL LAW REFORM: A COMPARATIVE STUDY OF UK AND US LEGISLATIVE RESPONSES - D. Sankar; Safoora Ahad (Masalah-Masalah Hukum, 2026)
The rapid development of artificial intelligence (AI) has transformed various sectors, but it has also created serious challenges for child protection, particularly in the digital environment. One of the most alarming developments is the emergence of AI-generated child sexual abuse material (CSAM), which enables the creation, possession, manipulation, and dissemination of abusive content without requiring direct physical contact with a child. This phenomenon forms part of a broader problem involving synthetic media, including non-consensual intimate deepfakes (NCID), which constitute a form of image-based sexual abuse and disproportionately affect women and girls. In India, the urgency of this issue is reflected in the rising number of cybercrimes against children. The National Crime Records Bureau (2022) reported a significant increase in such offences, while the National Cyber Crime Reporting Portal documented approximately 1.94 lakh CSAM-related cases by April 2024. India’s legal response to online child sexual abuse is primarily governed by the Protection of Children from Sexual Offences (POCSO) Act, the Information Technology Act, 2000, and the Bharatiya Nyaya Sanhita, 2023. However, these frameworks were not specifically designed to address the legal and evidentiary complexities posed by AI-generated, synthetic, morphed, and tool-assisted CSAM. The absence of explicit provisions on AI-generated CSAM creates gaps in enforcement, classification, liability, and regulatory oversight. This study adopts a qualitative doctrinal research methodology to examine the adequacy of India’s existing legal framework in addressing AI-generated CSAM. It critically analyses relevant statutory provisions, legal principles, and policy gaps, while also conducting a comparative assessment of recent legislative developments, including the UK’s Crime and Policing Act, 2026, and the U.S. Take It Down Act, 2025. Drawing on these comparative insights, the study argues that India must strengthen its legal, regulatory, and technological infrastructure to respond effectively to emerging AI-enabled cyber threats and to ensure robust protection of children in the digital age.